2016
DOI: 10.1093/bfgp/elw002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolic pathways using pathfinding approaches: a systematic review

Abstract: Metabolic pathways have become increasingly available for various microorganisms. Such pathways have spurred the development of a wide array of computational tools, in particular, mathematical pathfinding approaches. This article can facilitate the understanding of computational analysis of metabolic pathways in genomics. Moreover, stoichiometric and pathfinding approaches in metabolic pathway analysis are discussed. Three major types of studies are elaborated: stoichiometric identification models, pathway-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 105 publications
(120 reference statements)
0
12
0
Order By: Relevance
“…Since there was no statistical difference in the age and gender of pre‐FIT and FIT triage patients, we felt we were justified in comparing the two cohorts. The CRC detection rate of 3.2% in the FIT triage and 2.8% in the pre‐FIT group were similar suggesting that at the very least FIT was a safe triage method with rates similar to the 3.1% in the year 2019–2020 [ 11 ]. Pre‐COVID‐19, studies have demonstrated the potential value of FIT in CRC detection and triage; and since one study was from a local trust the local cancer alliance had even more confidence in the FIT as a triage tool [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since there was no statistical difference in the age and gender of pre‐FIT and FIT triage patients, we felt we were justified in comparing the two cohorts. The CRC detection rate of 3.2% in the FIT triage and 2.8% in the pre‐FIT group were similar suggesting that at the very least FIT was a safe triage method with rates similar to the 3.1% in the year 2019–2020 [ 11 ]. Pre‐COVID‐19, studies have demonstrated the potential value of FIT in CRC detection and triage; and since one study was from a local trust the local cancer alliance had even more confidence in the FIT as a triage tool [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…KEGG Mapper tools ( Kanehisa and Sato, 2020 ) also allow automatic assignment of enzymatic roles and pathway contextualization using genomes or proteomes as input and relies on the KEGG ontology to perform annotations based on sequence similarity. Other tools, reviewed elsewhere, allow additional curation and pathway-specific analysis to be performed once a draft reconstruction is attained ( Pitkänen et al, 2010 ; Abd Algfoor et al, 2017 ). Common to all described tools is their dependency upon a vocabulary of metabolic elements, or ontology, which depicts the complex, and often multi-level relationships among genes, proteins, enzymes, biochemical reactions, and regulators ( Stobbe et al, 2012 ).…”
Section: How To Prioritize Drug Targets In Pathogenic Bacteria?mentioning
confidence: 99%
“…While metabolism has traditionally been divided into metabolic pathways, subsystems of metabolism dealing with specific functions, it has become increasingly clear that metabolism operates as a highly integrated network [1,2]. The research on the metabolomics field has considerably increased since the early 2000s, from the analysis of single pathways [3][4][5][6], to the comparative analysis of a set of pathways [7], together with the metabolic networks dynamics [8,9]. All these studies are aimed to find out how the metabolism of different species has evolved in order to discern their associated metabolic functions (see for example [10,11]), which are important for studying diseases and identifying pharmacological targets (as explored in [12,13]).…”
Section: Introductionmentioning
confidence: 99%